2007
DOI: 10.1021/ol071052x
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic and Nonaromatic Pyriporphyrins

Abstract: Pyriporphyrins with three different orientations for the pyridine moiety have been prepared using a '3 + 1' strategy. The nonaromatic pyriporphyrins are stable so long as phenyl substituents are present at the meso-positions adjacent to the pyridine ring. An aromatic dihydropyriporphyrin with an external CO2Ph protective group has also been prepared from 2,4-pyridinedicarbaldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 30 publications
1
90
1
Order By: Relevance
“…82 X-ray crystallography confirmed that the complexes retained quinoidal structures and demonstrated that they exist in the zwitterionic forms shown in Scheme 59. 85,87 Lithium-halogen exchange with 3,5dibromopyridine, followed by reaction with aromatic aldehydes gave dicarbinols 150 (Scheme 61). 83 The proton NMR spectrum of 143 at room temperature showed the internal CH and NH protons at 1.89 and 4.67 ppm, and was consistent with a symmetical structure possessing a weak diatropic ring current.…”
Section: Aza-analogues Of Benziporphyrinsmentioning
confidence: 99%
“…82 X-ray crystallography confirmed that the complexes retained quinoidal structures and demonstrated that they exist in the zwitterionic forms shown in Scheme 59. 85,87 Lithium-halogen exchange with 3,5dibromopyridine, followed by reaction with aromatic aldehydes gave dicarbinols 150 (Scheme 61). 83 The proton NMR spectrum of 143 at room temperature showed the internal CH and NH protons at 1.89 and 4.67 ppm, and was consistent with a symmetical structure possessing a weak diatropic ring current.…”
Section: Aza-analogues Of Benziporphyrinsmentioning
confidence: 99%
“…[912] However, the benzene and pyridine moieties, respectively, are not fully conjugated into a porphyrin-like aromatic system. In contrast, oxypyriporphyrin 3 contains a porphyrin-like π-aromatic system incorporating the pyridone moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[25,38,39] Azuliporphyrins 6 show comparable diatropic character to the cross-conjugated NCPs 21, in both cases showing the internal CH resonances in proton NMR spectra near 3 ppm, although this property is greatly enhanced upon protonation. [25,39] Other systems that have been prepared using the '3 + 1' approach include N-confused pyriporphyrin 24, [40] oxynaphthiporphyrins 25 [41] and tropiporphyrins 8. [27,42] Further structural diversity can be introduced when modified tripyrrane structures are utilized in these syntheses (Scheme 2).…”
Section: Synthetic Methodologiesmentioning
confidence: 99%
“…[40] In 42b and 42c, a carbon atom is present in the macrocyclic core and these systems can be considered to be azabenziporphyrins. …”
Section: Synthetic Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation